Characterization of three species of the genus Coprotus (Ascomycota) by isozyme analysis - Suarez, Maria Eugenia (2006)
Identification of Coprotus species has never been an easy task. Their morphological and cultural characteristics are very similar and this often makes species delimitation very difficult. In this study we first identified 44 monosporic strains of three species of the genus (C. lacteus, C. niveus, C. sexdecimsporus) by using exclusively morphological and cultural characters; then, an extensive isozyme analysis was performed as an additional taxonomical technique. Eleven isozyme systems were tested.Six of them were chosen for the following analysis. The phenogram (UPGMA) and the 3D graphic (ordination technique) clearly separated the three species. The results of this study support the utilization of isozyme patterns as a valuable additional tool in delimiting Coprotus species based on traditional taxonomical methods.